2012
DOI: 10.1007/s10295-012-1195-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the saccharification capability of high-functional cellulase JN11 for various pretreated biomasses through a comparison with commercially available counterparts

Abstract: Although the capabilities of Trichoderma reesei cellulases have been greatly improved, these enzymes are still too costly for commercial use. The aim of this research was to assess the biomass saccharification capability of JN11, a recombinant cellulase, compared with that of the commercially available cellulases Accellerase 1500 and Cellic CTec. The activities of JN11, Accellerase 1500, and Cellic CTec were compared by using various types of cellulosic biomass, including rice straw, Erianthus, eucalyptus, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…From the specific activity data of the prepared enzyme used in this study, we found that JN11 has a greater BGL activity while the endo-and exo-cellulase activities were maintained and were comparable to the enzyme from its parental strain, PC-3-7 (Table S1). This is in accordance with the finding of Nakazawa et al (20) and Kawai et al (21), who reported that JN11 has higher saccharification capability for various pretreated biomass compared to that of PC-3-7 or other commercial enzymes. JN11 has since been considered as a promising enzyme for efficient ethanol production from lignocellulosic material.…”
Section: Discussionsupporting
confidence: 92%
“…From the specific activity data of the prepared enzyme used in this study, we found that JN11 has a greater BGL activity while the endo-and exo-cellulase activities were maintained and were comparable to the enzyme from its parental strain, PC-3-7 (Table S1). This is in accordance with the finding of Nakazawa et al (20) and Kawai et al (21), who reported that JN11 has higher saccharification capability for various pretreated biomass compared to that of PC-3-7 or other commercial enzymes. JN11 has since been considered as a promising enzyme for efficient ethanol production from lignocellulosic material.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, a negative band at 5980 cm −1 , attributable to aromatic framework vibrations, was detected, and the band relating to lignin at 6900 cm −1 also was negative. These results indicated that pretreatments that resulted in lower hemicellulose and higher lignin contents increased the saccharification ratio, which is consistent with a report published by our co-author Kawai [25]. These discussions on the regression coefficient can be summarized as follows: the hydrothermal treatment preferentially removes hemicellulose and results in higher lignin contents, as already reported [26,27], which leads to hydrophobic properties.…”
Section: Interpretation Of Calibration Model From Solid Analysis For supporting
confidence: 91%
“…26) Due to its high cellulase productivity, PC-3-7 is also used industrially to enhance lignocellulosic biomass y To whom correspondence should be addressed. Tel: +81-258-47-9407; Fax: +81-258-47-9400; E-mail: owataru@vos.nagaokaut.ac.jp conversion 28,29) and to reduce the cost of saccharification. Because several PC-3-7 derivative strains are being used industrially, the next focus of our research is optimization of strain cultivation parameters in order to improve cellulase production further.…”
Section: Identification Of Major Facilitator Transporters Involved Inmentioning
confidence: 99%